GIST as a Lead Point in Adult Intussusception: Study in a Tertiary Hospital - Akther, SM Quamrul; Reza, Syed Masud; Hoque, Md Mozammel; Mamun, Mohammad Abdullah Al; Ahmed, Farhad Uddin; Khan, Rafiul Karim; Ahmed, Nadim; Marium, Syeda Nishat (Journal of Shaheed Suhrawardy Medical College, 2020)
Introduction: Intussusception is very common in childhood between the ages of 5 months to 1 year. In adults it is a rarity, in whom it commonly presents with a nonspecific, repeated, chronic or subacute intestinal obstruction. Ninety percent of them have a variable number of secondary pathological ‘lead point’- from benign lesion to malignant.5 Objective: This study aims to find out the variations & the commonest ‘Lead points’ in rare adult intussusceptions. Methodology: Study period was from January 2015 to June 2019. All patients of adult intussusceptions, admitted in Shaheed Suhrawardy Medical college Hospital, were examined, investigated, & analysed peri-operative findings with post-operative histopathological results, in this prospective observational study. Result: In this study, among 15 patients, GIST found to be the commonest (46%) Lead point in adult intussusceptions. Others include Adenocarcinoma, Leiomyomatous polyp, Meckel’s Diverticulum, intestinal TB, etc. Male was mostly sufferer (67%). Ileoileal (II) variety was found more in male & Ileocecal (IC) variety in female. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 138-141